2018
DOI: 10.1111/jcpp.12877
|View full text |Cite
|
Sign up to set email alerts
|

Research Review: Intergenerational transmission of disadvantage: epigenetics and parents' childhoods as the first exposure

Abstract: Epigenetic intergenerational transmission, if at play in human populations, could have policy implications in terms of reducing the continuation of disadvantage across generations. Further research is needed to address this gap in the understanding of the perpetuation of compromised lives across generations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 115 publications
1
64
0
2
Order By: Relevance
“…The risks for certain psychopathologies may commence in the previous generation. The mechanisms underlying this intergenerational transmission are thought to be epigenetic in nature, potentially affecting the germ line, with far-reaching research, clinical, and societal implications, yet more remains to be understood (Scorza et al 2018).…”
Section: Summary Pointsmentioning
confidence: 99%
“…The risks for certain psychopathologies may commence in the previous generation. The mechanisms underlying this intergenerational transmission are thought to be epigenetic in nature, potentially affecting the germ line, with far-reaching research, clinical, and societal implications, yet more remains to be understood (Scorza et al 2018).…”
Section: Summary Pointsmentioning
confidence: 99%
“…In addition, individual differences in methylation levels may also be partially explained by genetic differences ( van Dongen et al, 2016 , 2018 ). Animal studies, and to a much more limited extent human studies, have shown that early adversity, including socioeconomic disadvantage and maternal care, affects gene expression and neural function, thereby contributing to intergenerational transmission (for reviews see Meaney, 2010 ; Scorza et al, 2019 ). These studies show how environmental factors, including parent–offspring interactions and social-economic disadvantage, affect epigenetic mechanisms as well as own (parenting) behavior For example, mothers’ experience of early interpersonal violence and maltreatment was found to be related to methylation of the promoter region of the glucocorticoid receptor gene NR3C1, which in turn related to neural response to interactions with their children ( Schechter et al, 2015 ).…”
Section: Epigenetic Processesmentioning
confidence: 99%
“…A wealth of animal research has demonstrated that stress-induced increases in corticosterone, a glucocorticoid, is tied to the dysregulation of offspring neurobiological systems governing stress responsivity (e.g., the hypothalamic–pituitary–adrenal axis; Glover, O’Connor, & O’Donnell, 2010) and reward-sensitivity (e.g., the mesolimbic dopamine system function; Gatzke-Kopp, 2011), both of which have been implicated as vulnerability factors for psychopathology. Several additional mechanisms (e.g., effects on women’s immune functioning, women’s health behaviors, epigenetics, and the quality of the postnatal environment) have been proposed and are discussed in greater detail elsewhere (e.g., Beijers et al, 2014; Gatzke-Kopp, 2011; Schlotz & Phillips, 2009; Scorza et al, 2018; Van den Bergh, Mulder, Mennes, & Glover, 2005). …”
Section: Emotion Dysregulation and Developmental Psychopathologymentioning
confidence: 99%